Narasi-Narasi Tentang Tubuh dalam Seni Rupa Kontemporer Indonesia Studi atas Karya-Karya Agus Suwage, Arahmaiani, Ivan Sagita, dan IGAK Murniasih - Acep Iwan Saidi (ITB Journal Publisher, LPPM ITB, 2007)
This paper ellaborates how human body is visualized in Indonesian contemporary art works, especially in the works of Agus Suwage, Arahmani, Ivan Sagita, and IGAK Murniasih. In their works, human body becomes the base of epistemological creation. Their different points of view and vocalizations resulted in the various themes of human body. Human body becomes full of social, political, psychological, philoshopical, empirical, and cultural values.